Synergistic Insecticidal Activity of Essential Oils from Ocimum basilicum and Ocimum gratissimum Against the Cowpea Weevil, Callosobruchus maculatus - Ayobami, Owolabi Tunde; Teslim, Ibrahim Oluwatomiwa; Adigun, Rafiu Toheeb; Catherine, Agu Chinwendu; Etetoghene, Omoko Awesome; Chiemezie, Okafor Izuchhukwu; Oyinlola, Dennis Olabode God’s favour (University of Brawijaya, 2026)
Protecting stored cowpea from Callosobruchus maculatus remains one of the most persistent challenges faced by smallholder farmers, who depend on this staple legume for both nutrition and income. Although several insects attack stored grains, C. maculatus is widely recognized as the most destructive pest of Cowpea, causing rapid quality loss and significant yield reduction. In this study, we investigated the insecticidal, repellent, and synergistic activities of individual and blended essential oils against adult C. maculatus. Fumigation, contact toxicity, and repellency assays were conducted under laboratory conditions (27 ± 2 °C, 65 ± 5% RH, and 12:12 h (L:D) photoperiod) to assess the impact of individual oils and formulated blends on pest mortality and behavior at varying concentrations of 0.2 – 0.5% over a period of 72 hrs. The oils varied considerably in potency. Ocimum gratissimum consistently emerged as the most effective, showing strong fumigant toxicity (48.87 ± 1.77%) and robust repellent action (100 ± 0%). Ocimum basilicum displayed moderate activity, whereas Citrus limon and Citrus sinensis produced minimal insecticidal effects (2.38 ± 1.65%) at comparable concentrations. Blended formulations, however, performed substantially better than single oils. The binary mixture FM1 exhibited the highest overall efficacy, resulting in rapid and near-total mortality (68.4 ± 1.99%), strong contact toxicity (70.0 ± 2.646%), and complete repellency within 2 hours of exposure period. Synergistic interactions were most evident in FM1, where observed effects exceeded those expected from individual components (SF; 1.94, CI; 0.005). Ternary (FM3) and quaternary (FM4) combinations also improved bioactivity, though to a lesser extent (SF; 1.73, CI; 0.045). These findings demonstrate the promise of Ocimum-based essential oil blends as eco-friendly, synergistic alternatives for protecting stored cowpea.